Validity and Reliability of Literacy Aptitude Test for Incoming Grade 7 Students Based on SOLO Taxonomy: Baliditi At Relayabiliti ng Pagsusulit Aptityud sa Literasi ng mga Mag-Aaral na Papasok Sa Ikapitong Baitang Ayon Sa Solo Taxonomy - Doctolero, Star Jewel (International Journal of Arts, Sciences and Education, 2025)
This study aimed to examine the validity and reliability of the Literacy Aptitude Test for incoming Grade 7 students, based on SOLO Taxonomy, conducted in three public schools in the Division of Koronadal. The test assessed literacy in listening, reading, and viewing, and evaluated comprehension according to the five cognitive levels under SOLO Taxonomy. To measure consistency, the test-retest method was used, and content validity was confirmed through expert evaluation, utilizing the Content Validity Index (CVI) and face validity measures. Results revealed that students excelled in listening, while viewing was their weakest skill, indicating a need for further development in that area. Significant correlations were found between listening, reading, and viewing, suggesting that improvements in one skill support progress in others. However, the lower correlation for viewing highlights the need for targeted instructional reinforcement. The test demonstrated strong validity and reliability, supporting its use for evaluating literacy skills and guiding targeted interventions, particularly to strengthen viewing skills and promote balanced literacy development.